Recent Advances and New Perspectives in Managing Macular Degeneration - Gunvant Davey, Pinakin (IntechOpen, 2022)
Macular degeneration is a blinding disease with huge socioeconomic costs. This book presents a comprehensive overview of macular degeneration, including age-related macular degeneration (AMD). Chapters address such topics as the disease state of macular degeneration, diagnosis and management of AMD, treatment considerations, and vision rehabilitation. It is a useful resource for both novice readers and experts in the field.